Compliance in medication control of hypertension patients during the transition period of the COVID-19 pandemic - Priscilla, Hilary; Semiarty, Rima; Masnadi, Nice Rachmawati; Abdiana; Fadrian (BKM Public Health and Community Medicine, 2023)
Purpose: This study aims to determine the relationship between adherence to medication control and blood pressure in hypertensive patients at the Talawi Public Health Center, Sawahlunto, during the transition period of the COVID-19 pandemic. Methods: This observational analytic study with a cross-sectional design was conducted from May to June 2023 at the Talawi Public Health Center, Sawahlunto, with 83 research subjects. The research instrument used primary data from the MMAS-8 questionnaire with short interviews and secondary data in medical records of hypertension patients at the Talawi Public Health Center, Sawahlunto, in 2021–2023. The research results were analyzed by chi-square test. Results: The results of this study were that the majority of hypertensive patients were not compliant in controlling their medication (65.1%), and the majority of hypertensive patients had uncontrolled blood pressure (61.4%). Conclusion: This study concludes a significant relationship between adherence to medication control and blood pressure in hypertensive patients at the Talawi Public Health Center, Sawahlunto (p=0.041).